Revisiting ESG Performance in Islamic Capital Markets: Sustainable Leadership as a Strategic Moderator - Happy Sista Devy; Syifa Rohmah; Adel Mohammed Sarea; Arina Roudhotul Jannah (Indonesian Journal of Applied Accounting and Finance, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) practices on projected financial performance using Return on Assets (ROA) and market performance measured by stock prices, with sustainable leadership as a moderating variable. The research subjects are companies listed on the SRI-KEHATI Index and the Indonesian Sharia Stock Index. The research method used is quantitative with a causality approach, using multiple regression tests and Moderated Regression Analysis (MRA) through E-Views software. The research subjects are companies listed on the SRI-KEHATI Index and the Indonesian Sharia Stock Index. The research method used is quantitative with a causality approach, using multiple regression tests and Moderated Regression Analysis (MRA) through E-Views software. The results show that ESG practices have a significant positive effect on financial performance (ROA), but a significant negative effect on stock prices. Originality/Values: These findings indicate that although the implementation of ESG can improve company efficiency and profitability, the high implementation costs can actually cause negative investor perceptions in the short term. Furthermore, sustainable leadership was found to moderate the effect of ESG on ROA, but not on stock prices. Thus, the results of this study emphasize the importance of an ESG implementation strategy that is integrated with sustainable leadership in order to improve financial performance without reducing the company's market value.